ANALISIS RETRIBUSI PEMAKAIAN KEKAYAAN DAERAH SEBAGAI SUMBER PENDAPATAN ASLI DAERAH KABUPATEN KUANTAN SINGINGI - Rika Rivana; Syapsan Syapsan; Hendro Ekwarso (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this study was to determine the potential and contribution of the Regional Wealth Usage Retribution in Kuantan Singingi Regency in preparing a comprehensive and more realistic budget plan. know the management of wealth which includes procurement, utilization, maintenance and supervision in optimizing the acceptance of the Retribution for the Use of Regional Wealth, the factors that affect the realization of the Retribution for the Use of Regional Wealth in Kuantan Regency. Data collection technique : Observation, Interview, Questionnaire, Documentation. Methods of data analysis using quantitative descriptive. The results of the study show Potential Retribution for Use of Regional Wealth in Kuantan Singing Regency land use of 298,638,310.86, the use of the building is Rp. 355,368,183.33 and use of vehicles/heavy equipment 2,729,160,000,-. While the contribution of land use is 0.60%, for building use 2.74% and for use of vehicles/heavy equipment is 9.54%. Based on the criteria, the contribution is still very low compared to other PAD sources. Management of regional wealth which includes procurement, utilization, maintenance and supervision in optimizing the acceptance of the Retribution for the Use of Regional Assets together (simultaneously) variable planning (X1), maintenance and supervision variables (X2), and utilization (X3) have a significant effect on the retribution variable for the use of regional wealth. The management of regional property is good, but it needs to be optimized again so that planning, maintenance and supervision as well as its utilization can make a major contribution in increasing regional original income sourced from retribution for the use of regional assets.